Program Pendampingan Tentang Hak Anak dalam Rangka Mencegah Perundungan (Bullying) dan Kekerasan Seksual di Lingkungan Sekolah: Pengabdian - Ekawestri Prajwalita Widiati; Zendy Wulan Ayu Widhi Prameswari; Amira Paripurna; Ajeng Anggraeni (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Understanding juvenile delinquency involves exploring the complex interactions between individual, family, social, and environmental factors that can influence the likelihood of youth engaging in unlawful activities. Given the critical developmental stage of adolescence, addressing and preventing juvenile delinquency is extremely important at this phase. The profile of Madiun Regency at East Java, as the